Macrophage-Secreted S100A4 Supports Breast Cancer Metastasis by Remodeling the Extracellular Matrix in the Premetastatic Niche. (20th April 2022) - Qi, Yana; Zhao, Tingting; Li, Ranran; Han, Mingyong
Abstract : Metastasis is the major cause of cancer-related mortalities. A tumor-supportive microenvironment, also known as the premetastatic niche at secondary tumor sites, plays a crucial role in metastasis. Remodeling of the extracellular matrix (ECM) is essential for premetastatic niche formation, especially for circulating tumor cell colonization. However, the underlying molecular mechanism that contributes to this effect remains unclear. Here, we developed a lung metastasis model with 4T1 breast cancer cells and found that the metastasis critically depended on the early recruitment of macrophages to the lung. Disruption of macrophage recruitment reduced fibroblast activation and lung metastasis. Furthermore, we identified the secreted protein S100A4, which is produced by M2 macrophages and participates in fibroblast activation and ECM protein deposition via the ERK signaling pathway. Collectively, these results indicate that recruiting S100A4-expressing inflammatory macrophages plays a vital role in ECM remodeling in the premetastatic niche and may act as a potential therapeutic target for breast cancer lung metastasis.